NO BETTER, OR WORSE: ATTRIBUTES OF TEACHING COMPETENCE IN STUDENT PERCEPTION (SciELO Preprints, 2021)
This research has the purpose of verifying the perception of the students regarding the attributes or skills of teaching quality. We assume a concept of competence that is not limited to the measurement of objective results, but that emphasizes more the importance of recognition or perception of others for their evaluation. For analysis, students from the administration course of two units of a private Higher Education Institution in Curitiba and metropolitan region were selected. The research technique chosen was the registration of critical incidents. The results indicate some characteristics of the teaching quality, such as diversification of teaching strategies; participation of students; attention and incentive of the teacher to learning. Some characteristics of the lack of teaching quality are summarized in the domain of content but not being able to explain; monotonous class; and the lack of good conduct in the relationship with the students. The identified attributes of competence can compose different teaching styles.